2021
DOI: 10.5897/jhf2020.0657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NPK fertilizer rates on secondary metabolites of pepino melon (Solanum muricatum Aiton)

Abstract: Secondary metabolites are bioactive compounds which are synthesized naturally in all plant parts. The quality and quantity of secondary metabolites produced by plants differ depending on the plant and environmental conditions under which they are produced. The purpose of the study was to investigate the effects of nitrogen, phosphorous and potassium (NPK) fertilizer (17:17:17) rates (0, 100, 200, 300 and 400 kg ha-1) on the production of secondary metabolites in field and greenhouse grown pepino melons (Solanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The combination of three NPK increased the polyphenol content and affected the antioxidant potential of C. xanthorrhiza (except for DPPH and FRAP analysis). However, Our findings tend to be different to other experimental results [30] reported that the phenolic content in the control (untreated) treatment of Pepino melon was remarkably higher than in the NPK treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The combination of three NPK increased the polyphenol content and affected the antioxidant potential of C. xanthorrhiza (except for DPPH and FRAP analysis). However, Our findings tend to be different to other experimental results [30] reported that the phenolic content in the control (untreated) treatment of Pepino melon was remarkably higher than in the NPK treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…First, although the research results of Radušienė et al [38] stated a decrease in the levels of phenolic compounds due to nitrogen treatment, on the other side, there was a significant increase in naphtodianthrones and emodin, both of which are derivatives of anthraquinone. It is in line with Carol et al [30] which stated a decrease in the amount of TPC Pepino melon due to NPK treatment, but a drastic increase in lutein, lycopene, and β-carotene. Furthermore, the research of Narvekar and Tharayil [46] stated that the nitrogen supply increased the quantity of proanthocyanidins in strawberries, one of the phenolic oligomers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation